Effectiveness of Using Wire Rope Slings in Improving the Stability of Cantilever Retaining Walls - Tarigan, Rasdinanta; Parman; Harahap, M. Ari Subhan; Amrizal (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
A slope is a land surface that slopes and forms a certain angle to a horizontal plane. In a place where there are two land surfaces of different heights, there will be forces that push so that the higher ground tends to move downwards which is called the potential force of gravity which causes landslides. Landslides on a slope can cause loss of life and property and can hamper the economy of an area. Cantilever walls are often used as retaining walls to avoid landslides. The cost used in the construction of cantilever wall retaining walls is quite expensive. For cost efficiency of the cantilever wall construction, it is necessary to use cantilever wall reinforcement using wire rope sling. In this study, cantilever wall retaining walls were modelled with or without the use of wire rope slings. The research location is Jl. Gelugur Rimbun, Ps x Kutalimbaru Kab. Deli Serdang. Based on the results of laboratory testing, the soil classification at the location is clay (CL). According to the analysis, the use of wire rope slings contributes to an increase in the factor of safety (FS) of overturning by 12.500% - 50.026%. While increasing the factor of safety (FS) sliding by 4.165% - 16.627%. An increase in the factor of safety (FS) bearing capacity of 17.222% - 36.109%. The greatest effect of the use of wire rope slings occurs in overturning stability by 50.026%. The use of wire rope slings can reduce the dimensions of cantilever retaining walls.